The kidney injury biomarker profile of patients with lupus nephritis remains unchanged with the second-generation calcineurin inhibitor voclosporin - Palmer, Biff F.; Tumlin, James A.; Radhakrishnan, Jai; Rehaume, Linda M.; Cross, Jennifer L.; Huizinga, Robert B. (Frontiers in Nephrology, 2025)
ObjectivesKidney injury in patients with lupus nephritis (LN) results in pro-fibrotic biomarker expression, a manifestation also observed with calcineurin inhibitor (CNI) therapy. The second-generation CNI, voclosporin, is approved in the United States and Europe for the treatment of patients with active LN in combination with background immunosuppression, based on successful outcomes from the global phase 2 AURA-LV and phase 3 AURORA 1 studies, which demonstrated the efficacy of voclosporin across diverse racial and ethnic populations, and encompassing multiple biopsy classes of LN, alongside a favorable safety profile. This post hoc analysis examined changes from baseline levels of serum and urinary biomarkers, including pro-fibrotic biomarkers, in a cohort of patients from the parent AURORA 1 studyMethodsSamples were analyzed from a cohort of patients in AURORA 1 treated with voclosporin (23.7 mg twice daily, n=57) or placebo (n=59) in combination with mycophenolate mofetil (MMF) and low-dose glucocorticoids, including in a subgroup of patients that experienced a ≥30% decline from baseline in estimated glomerular filtration rate (voclosporin, n=26; placebo, n=20).ResultsThe addition of voclosporin to MMF and low-dose glucocorticoids for the treatment of LN did not result in significant differences in normalized urinary concentrations of KIM-1, TGF-β1, MCP-1, or NGAL, biomarkers indicative of renal fibrosis and kidney damage, when compared to MMF and low-dose glucocorticoids alone.ConclusionThese findings further support the safety of voclosporin for the treatment of LN in adult patients.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT03021499; EudraCT, identifier 2016-004045-81.